The Role of Parents and Schools in Building Children’s Character of Responsibility - Lutfi Firdausi (Agrapana Media, 2025)
This study examines the development of children’s sense of responsibility through the combined and complementary roles of parents and schools. Responsibility is a core moral character that requires consistent guidance, modeling, and reinforcement across multiple environments. Parents act as the primary moral educators by demonstrating responsible behavior, providing clear expectations, fostering open communication, and ensuring consistency between household rules and broader social norms. Such parental practices cultivate intrinsic motivation and moral reasoning in children, allowing them to act responsibly even without direct supervision. Schools, as structured and socially interactive environments, serve as secondary yet essential platforms for reinforcing responsibility. Through formal curricula, extracurricular activities, classroom management, and a supportive moral climate, schools provide practical opportunities for children to apply moral knowledge, develop accountability, and internalize socially shared standards. The study highlights that the highest effectiveness in character formation is achieved when parents and schools collaborate harmoniously. Open communication, joint programs, and aligned values between family and educational institutions create a coherent moral ecosystem, preventing inconsistencies that could confuse children’s moral development. Cultural and religious contexts, particularly in Indonesia, further enrich this process by linking moral responsibility to spiritual and communal obligations. Overall, this study emphasizes that sustainable character education requires the integration of family, schools, and local cultural values, transforming responsibility from a taught concept into a lived habit that shapes both personal and social conduct.